Unemployment and Labour Market Policies : Empirical Analysis for Poland - Wiśniewski, Zenon; Maksim, Monika (Olsztyn Economic Journal, 2017)
This article presents the development of unemployment and labour market policies in Poland in the period 2005-2015. The paper focuses on the nature and structure of unemployment, expenditure from the Labour Fund, active labour market policy instruments and participants. Active labour market policy evaluation was performed quasi-experimentally and was based on a propensity score matching method. The effects of the policies were evaluated based on information concerning the unemployed taken from the Syriusz database.